Diffusion influence on the speed of pulsating travelling fronts in KPP-Type problems - Valdez, Adrian Roy L.; Navarro, Milagros P. (Quezon City Department of Mathematics, College of Science, University of the Philippines Diliman, 2007)
Front propagation is a phenomenon which occur in many scientific areas such as chemical kinesis, combustion, biological invasion and population dynamics, transport in porous media, and industrial deposition process.
Thesis (Ph.D. Mathematics)--University of the Philippines Diliman
Keywords: Diffusion processes